2014
DOI: 10.5937/opmed1402025s
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk for falls in elderly

Abstract: Introduction: Elderly persons have higher risk for falls, compared to younger population. Although no single risk factor causes all falls, a great deal of risk factors to which an individual is exposed, i.e. osteoporosis, lack of physical activity, impaired vision, usage of drugs, living settings etc, can be treated.Objective: To investigate the risk for falls in elderly patients treated in Family medicine teaching center (ECPM), Primary Health Care Center Banja Luka.Method: This prospective study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Stanetić et al [34] pointed out that the greatest risk of falls was associated with diuretics and NSAIDs that coincides with our results. Benzodiazepines were used by 50 (33.3%) patients, and it did not affect significantly the risk of falls, which is opposite to our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Stanetić et al [34] pointed out that the greatest risk of falls was associated with diuretics and NSAIDs that coincides with our results. Benzodiazepines were used by 50 (33.3%) patients, and it did not affect significantly the risk of falls, which is opposite to our results.…”
Section: Discussionsupporting
confidence: 92%
“…In their study, Stanetić et al [34] showed that hypertension and diabetes, as isolated diseases, have no significant effects on the risk of falls in the elderly, but considering that patients suffering from these diseases are mainly associated with comorbidity, the risk of falling increases with age. All patients suffering from diabetes mellitus also had hypertension.…”
Section: Discussionmentioning
confidence: 99%